Simulation-based comparative analysis of different chassis configurations of hybrid fuel cell vehicle - Nam Nguyen Tien; Hieu Nguyen Van; Vinh Nguyen Duy; Hoang Phuc Trinh (International Journal of Thermofluids)
This manuscript examines the chassis design of compact electric vehicles fueled by fuel cells, focusing on ensuring structural strength, optimizing weight, and integrating fuel cell systems. Consequently, a thorough design framework is created, which includes the selection of materials, study of the structure, and safety concerns. We employ advanced computational techniques and finite element analysis to create models and simulate numerous design scenarios, guaranteeing optimal performance under diverse operating circumstances. The chassis is designed to meet the precise needs of fuel cell systems, such as hydrogen storage and safety measures. The findings indicate that a meticulously engineered chassis can greatly improve the effectiveness and security of compact electric vehicles propelled by fuel cells. The findings contribute to the wider field of sustainable vehicle design and offer practical insights for future research and development in electric vehicle (EV) technology. Furthermore, this thesis asserts that incorporating fuel cell technology into the chassis design of compact electric vehicles offers a feasible route to achieve more sustainable and efficient urban transportation options.